ELECTIONS IN HUNGARY AND IN OTHER COUNTRIES UNDER SPECIAL LEGAL ORDER – ESPECIALLY DURING THE PANDEMIC - Téglási, András; Nagy, Attila Mihály (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The paper examines what was Hungary’s and other European countries’ answer to the collision between the exercise of the right to vote and the measures of public health meant to guarantee the right to health. The paper focuses on the effects that the epidemic triggered by the coronavirus had on Hungary’s and other countries’ elections and electoral processes. Overall, managing the situation posed a serious challenge to all decision makers throughout the world, and countries holding general elections during the pandemic faced particular difficulties. In countries where decision was taken to hold (general) elections (often after postponement), increased measures of protection were implemented during both the campaign and the voting. However, experience shows that despite all these efforts fewer citizens turned out to vote than before the pandemic. This faces countries which are about to organize general elections with a serious dilemma. In fact, decision makers have to ensure the right to vote for all those wanting to exercise it on the one hand, and on the other hand this has to be done amid circumstances that would not expose voters’ health to danger. In order to reach a higher turnout, softening electoral requirements (concerning, for example, the very process of casting the vote) seems to be an obvious solution, but the principle of proportionality has also to be taken into account to preserve the integrity of elections.